The investigation on the effects of free and dependent housing types on cow foot diseases and claw deformations in turkey, mus province - Istek, Ozmen; Han, Mehmet Cengiz; Sagliyan, Aydin (My University, 2014)
This study aims to determine the effects of different housing types on cow foot diseases and claw deformations in Turkey, Mus Province. The study group consisted of 1292 animals which were randomly selected and sheltered in 48 free and 33 dependent stables between July 2011 and August 2012. The rate of deformity observed in claws of cows in free stables was found to be 61.48% while this rate was 38.16% in dependent stables. The studies found the rates of cow claw deformities in free stables as follow: 2.3% blunt claw, 3.50% scissors claw, 6.01% sharp claw, 3.13% split claw, 2.63% flat and plump claw and 4.38% twisted claw. The rates in dependent stables are as follow: 1.62% blunt claw, 1.83%) scissors claw, 3.65% sharp claw, 1.62% split claw, 1.82% flat and plump claw and 1.22% twisted claw. The rates of foot diseases of cows in free stables were found to be as follow: 3.13% heel erosion, 2.13% heel apse, 1.00%) interdigitalhyperplasia, 1.15% interdigital phlegmon, 1.38% laminitis, 1.00%) digital dermatitis, 2.63% white line disease, 4.01 % heel and plantar crush. These rates in dependent stables are as follow: 1.83%) heel erosion, 1.22%) heel apse, 0.81%) interdigital hyperplasia, 0.61% interdigital phlegmon, 2.2% laminitis, 0.81%) digital dermatitis, 0.81%) white line disease, 1.42% heel and plantar crush. © Medwell Journals, 2014.
Keywords: Claw lesions; Foot diseases; Free stalls; Prevalence; Tie stalls